A MELACAK JEJAK PEREKONOMIAN INDONESIA: DARI WARISAN KOLONIAL HINGGA ERA GLOBALISASI - Santoso, Hilmy (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
P Economic growth is one of the goals to be achieved by the State in improving welfare (welfare state), so that the acceleration of economic growth becomes important and strategic for a country in the context of the development process, even an indicator of the successful performance of an economy. The purpose of this article is to follow the progress of the Indonesian economy from the pioneering period to the globalisation period. By understanding this journey, we can gain further knowledge of how arrangements, fundamental changes, and relationships with business sectors around the world have shaped the Indonesian economy today. The research method used is a heuristic strategy where this is an exploratory approach that emphasises gathering information through various important sources and investigating information to create important goals. The results of the research found that the magnitude of the influence of the heritage of the ancestors on economic growth can provide progress in the future. History records where the strong impact of the Dutch limited development policy to the progress towards an open and universally connected economy, these traces reflect massive changes in monetary aspects, strategies, and global relations. From old demands, new demands, financial emergencies, to times of change. It shows that Indonesia has experienced various phases of ups and downs in economic growth.